“There is no peace when you are excluded”: exploring peace and peacebuilding with children and youth affected by armed violence - Baillie Abidi, Catherine (Frontiers in Psychology, 2025)
The global community is becoming increasingly fragile, plagued with intensifying armed violence, fracturing democratic governance processes, diminishing commitments and actions to protect basic human rights, and raging climate crises. Amid these complexities, children and youth are disproportionately impacted, and all signs point to increased precarity of their rights. Young people affected by armed violence are particularly suffering, thus understanding their rights and needs during and post conflict is essential to building effective peace and security. This research features the peace perspectives of 50 children and youth, all impacted by armed violence, and demonstrates the power of listening to young people’s visions for peace. The key findings illustrate the importance of interpersonal peace, learning peacebuilding skills, and the essential role that children and youth play in building peace in their homes, schools, and communities. Recommendations for meaningful child engagement in the development of a Children, Peace, and Security Agenda are featured.